How childhood adversities shape minds and lives: an analysis across the affective-to-psychotic spectrum - Greiner, Sophie-Kathrin; Pons, María Dech; Ablimit, Ayimnisagul; Brauße, Elisa; Adorjan, Kristina; Budde, Monika; Heilbronner, Maria; Heilbronner, Urs; Kalman, Janos L.; Navarro-Flores, Alba; Kohshour, Mojtaba Oraki; Reich-Erkelenz, Daniela; et al. (Psychiatry research, 2025)
Adverse childhood experiences (ACE) contribute significantly to mental disorders. While existing research has primarily focused on specific diagnostic categories, a comprehensive understanding of how childhood trauma interacts with biological factors, symptom severity and functioning requires a broader perspective. Therefore, this study adopted a cross-diagnostic approach to examine the impact of ACE on quality of life (QoL), psychosocial functioning, and symptom burden by analyzing data from the PsyCourse Study, a longitudinal, multicenter research project conducted in Germany and Austria. We used multivariate linear regression models and cluster analysis to evaluate data from 725 participants with affective and psychotic disorders and healthy controls who completed the self-assessed Childhood Trauma Screener (CTS) during the course of the study. The results showed that across diagnoses, QoL was significantly impacted by ACE, particularly emotional neglect. An ablation study revealed that 2.3 % to 6.2 % of the variability in QoL domains could be attributed to ACE. Across diagnoses, symptoms of depression were significantly associated with ACE, especially emotional abuse, but psychotic and manic symptoms were not. Polygenic risk scores (PRS) did not emerge as significant predictors for any examined outcomes. Cluster analysis revealed distinct symptom profiles: Averaged over time, patients with less trauma exposure were rather in the subclinical than in the clinically ill clusters. We conclude that the pervasive influence of ACE on disease severity should be considered when evaluating and treating patients with affective and psychotic disorders.
Online verfügbar: 13. Mai 2025, Artikelversion: 26. Mai 2025
Gesehen am 18.08.2025